Silyl Ethers as Latent Pronucleophiles in Enantioselective Lewis Base Catalyzed Synthesis of Allylic Ethers from Allylic Fluorides - Lange, Markus; Barakat, Abdulrahman; Vilotijevic, Ivan (Synlett, 2024)
Allylic ethers are a common occurrence in natural products, and are often used as intermediates in target-oriented synthesis. Their synthesis often relies on the use of transition-metal catalysts. Here, we report an organocatalytic method for the allylation of O-centered nucleophiles, the Lewis base catalyzed allylation of silyl ethers with allylic fluorides. The method relies on the concept of latent pronucleophiles in Lewis base catalysis to overcome common limitations in substrate scope, even permitting the allylation of sterically congested O-pronucleophiles. When chiral Lewis base catalysts are used, the allyl ethers are produced in an enantioenriched form through kinetic resolution of fluorides, where the stereoselectivity is determined by the chiral catalyst.
Keywords: Lewis base catalysis; allylation; allyl ethers; silyl ethers; stereoselectivity